IS "HAPPY NEW YEAR AND MARRY CHRISTMAS!" FOR EVERYONE? HOW WE ARE IN THE MOOD DURING THE HOLIDAYS (Heritage, 2023)
The festive atmosphere that abounds at the end of one year and the beginning of another is inevitably associated with happiness, joy, excitement and other positive emotions. It is a period of emotional, but also material exchanges with family members, friends, colleagues... A large number of people in the Republic of Serbia, in this time of year, go on a short vacation from work and obligations, wishing each other happy holidays. However, this is also the period when the achievements of the previous year are summed up, when people become aware of their failures, the small number of close people they can rely on and who can provide them with love and support. The main goal of this research was to examine the mood of people in Serbia during these holidays, i.e. do wishes for a good mood correspond to reality. We surveyed 450 adults aged 18-68, 65% of whom were women, using an online questionnaire. In addition to sociodemographic data, respondents also provided answers to items from the Brief Mood Introspection Scale. The results showed that positive moods are significantly more pronounced than negative ones, and that the largest number of respondents feel emotions around New Year's and Christmas: full of love, happy, satisfied and active. However, nervousness, tension, fatigue, oversaturation and other negative emotions are present in a significant number of respondents. We can conclude that one of four, or one of five persons don’t feel happiness, satisfaction or other positive emotion during these holidays, but they feel some negative emotions. Those results are important because some earlier researches showed that rate of suicide (Barker, Gorman & De Leo 2014:122-126) and substance abuse (Vidal-Infer et al, 2007: 134-141) are higher in New Year and Christmas season. In present research we didn`t obtained any significant differences regarded to sex or education level of the respondents. Finally, we have to assume that there are one group of people who are in risk to feel bad during holidays and to have a lower mental health. Professionals and authorities should pay additional attention on this vulnerable people and try to improve their social inclusion and support.
Keywords: mood, Christmas, New Year.